Increasing donor kidney age significantly aggravates the negative effect of pretransplant donor-specific anti-HLA antibodies on kidney graft survival - Betjes, Michiel G. H.; Kal-van Gestel, Judith A.; Roelen, Dave; Kho, Marcia M. L.; Heidt, Sebastian; de Weerd, Annelies E.; van de Wetering, Jacqueline (Frontiers in Immunology, 2025)
Background and hypothesisThe presence of donor-specific anti-HLA antibodies before kidney transplantation (preDSAs) is associated with decreased graft survival. The hypothesis that increasing donor kidney age is negatively associated with the impact of preDSA on graft survival was investigated.MethodsOutcome of kidney transplantation in a single center cohort of 2,024 patients transplanted between 2010 and 2020 with a follow-up of at least 3 years was analyzed to assess this relation.ResultsDSAs before transplantation were present in 14% of recipients and showed an independent association with graft loss. The preDSA against HLA class I (2%) or class II (7%) had an adjusted hazard ratio (HR) for death censored graft failure of 5.8 (95% CI 4.4–7.7), while the combination (5%) had an HR of 18.6 (95% CI 13.8–25.1). The preDSA-associated increase in graft failure was caused primarily by an increase in the incidence of antibody-mediated rejection (ABMR), intragraft thrombosis, and primary non-function. These effects were observed more frequently in the deceased donor kidney transplantations compared to living donor kidney transplantations. The incidence of ABMR was not associated with donor kidney age. However, increasing donor kidney age significantly aggravated the negative effect of preDSA on graft survival. For instance, recipients aged ≥65 years transplanted with a deceased donor kidney aged ≥65 years had an uncensored 1- and 3-year graft survival of 83% and 67%, respectively, if transplanted without DSA. This decreased to 56% and 35% if transplanted in the presence of DSA. For comparison, recipients aged ≥65 years of a deceased donor kidney aged <65 years had an uncensored 1- and 3-year graft survival of 92% and 78%, respectively, without preDSA, and if transplanted with preDSA, this decreased to 77% and 69%, respectively.ConclusionsThe negative effect of circulating DSA at the time of transplantation on both early and late death-censored graft survival is heavily influenced by donor age.